Calcium silicate-based root canal sealers: a literature review - Miyoung Lim; Chanyong Jung; Dong-Hoon Shin; Yong-bum Cho; Minju Song (Restorative Dentistry & Endodontics, 2020)
Epoxy resin-based sealers are currently widely used, and several studies have considered AH Plus to be the gold-standard sealer. However, it still has limitations, including possible mutagenicity, cytotoxicity, inflammatory response, and hydrophobicity. Drawing upon the advantages of mineral trioxide aggregate, calcium silicate-based sealers were introduced with high levels of biocompatibility and hydrophilicity. Because of the hydrophilic environment in root canals, water resorption and solubility of root canal sealers are important factors contributing to their stability. Sealers displaying lower microleakage and stronger push-out bond strength are also needed to endure the dynamic tooth environment. Although the physical properties of calcium silicate-based sealers meet International Organization for Standardization recommendations, and they have consistently reported to be biocompatible, they have not overcome conventional resin-based sealers in actual practice. Therefore, further studies aiming to improve the physical properties of calcium silicate-based sealers are needed.